Antibodies as drugs—a Keystone Symposia report. Issue 1 (16th November 2022) - Cable, Jennifer; Saphire, Erica Ollmann; Hayday, Adrian C.; Wiltshire, Timothy D.; Mousa, Jarrod J.; Humphreys, David P.; Breij, Esther C. W.; Bruhns, Pierre; Broketa, Matteo; Furuya, Genta; Hauser, Blake M.; Mahévas, Matthieu; et al.
Abstract: Therapeutic antibodies have broad indications across diverse disease states, such as oncology, autoimmune diseases, and infectious diseases. New research continues to identify antibodies with therapeutic potential as well as methods to improve upon endogenous antibodies and to design antibodies de novo . On April 27–30, 2022, experts in antibody research across academia and industry met for the Keystone symposium "Antibodies as Drugs" to present the state‐of‐the‐art in antibody therapeutics, repertoires and deep learning, bispecific antibodies, and engineering. Abstract : Therapeutic antibodies have broad indications across diverse disease states such as oncology, autoimmune diseases, and infectious diseases. New research continues to identify antibodies with therapeutic potential as well as methods to improve upon endogenous antibodies and to design antibodies de novo. On April 27‐30, 2022, experts in antibody research across academia and industry met for the Keystone symposium "Antibodies as Drugs" to present the state‐of‐the‐art in antibody therapeutics, repertoires and deep learning, bispecific antibodies, and engineering.